PEMENUHAN HAK-HAK PEKERJA WAKTU TERTENTU PADA PT. WIRATAMA JAYA PERKASA DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Frisri, Alika Nanda; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Fulfillment of certain workers' rights at PT. Wiratama Jaya Perkasa which is not implemented is aform of violation against the applicable law according to the law number 13 of 2003 on employmentArticle 78 has clearly stated that "employers who employ workers exceed the working hours referred to inArticle 77 paragraph (2) must qualify "but in practice there are still many entrepreneurs who forget one ofthe rights of workers / laborers.The main issues of this study are How to fulfill the right of workers / laborers in PT Wiratama JayaPerkasa and What are the factors inhibiting the fulfillment of the right of workers / laborers in PTWiratama Jaya Perkasa.This research employs empirical law research method, that is research done by direct location andusing data collection tool in the form of interview. The data obtained were analyzed using qualitativeapproach which yielded descriptive data that is what respondents responded verbally and the realtreatment to give a picture of a complete, detailed and clear reality to the outsouring implementation at PTWiratama Jaya Perkasa in fulfilling the rights of certain time workers based on the law number 13 of 2003on employment.The results of research conducted on PT Wiratama Jaya Perkasa in the fulfillment of the rights ofcertain time workers have not been implemented entirely in accordance with the prevailing provisions, soin practice there are obstacles both derived from the internal PT Wiratama Jaya Perkasa or externalfactors outside of PT Wiratama Jaya Perkasa.Keywords: Fulfillment of Rights-Specific Time Agreement